Clinical and genomic features of Mycobacterium avium complex: a multi-national European study - Wetzstein, Nils; Diricks, Margo; Anton, Thomas B.; Andres, Sönke; Kuhns, Martin; Kohl, Thomas A.; Schwarz, Carsten; Lewin, Astrid; Kehrmann, Jan; Kahl, Barbara C.; Schmidt, Annika; Zimmermann, Stefan; et al. (Genome medicine, 2024)
The Mycobacterium avium complex (MAC) comprises the most frequent non-tuberculous mycobacteria (NTM) in Central Europe and currently includes twelve species. M. avium (MAV), M. intracellulare subsp. intracellulare (MINT), and M. intracellulare subsp. chimaera (MCH) are clinically most relevant. However, the population structure and genomic landscape of MAC linked with potential pathobiological differences remain little investigated.